Identification of ionospheric scintillation in the low-latitude African sector using a commercial CubeSat constellation - Mohanty Shradha; Hoque M. Mainul; Angling Matthew J. (Journal of Space Weather and Space Climate, 2025)
Radio occultation (RO) measurements performed by Global Navigation Satellite System (GNSS) receivers onboard low-earth orbit (LEO) satellites are commonly used for a variety of atmospheric applications, including ionospheric and space weather studies. We have used high-rate (50 Hz) GNSS-RO measurements from Spire’s CubeSat constellation to identify ionospheric scintillation over the low-latitude African sector. Three scintillation events are analyzed using independent electron density and total electron content measurements from the Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC)-2 mission, nighttime disk images from the Global-scale Observations of the Limb and Disk (GOLD) mission, and plasma parameters from the Ionospheric Connection Explorer’s (ICON) Ion Velocity Meter (IVM) instrument. We have found simultaneous occurrences of amplitude scintillation in Spire’s GNSS-RO measurements and signatures of ionospheric irregularities in the colocated measurements of COSMIC-2, GOLD, and ICON missions during ionospherically perturbed post-sunset hours. During ionospherically quiet periods, no scintillation or ionospheric irregularity was detected by any of the different sensors. We have also performed a long-term statistical analysis of low-latitude equatorial GNSS-RO data from the Spire and COSMIC-2 constellations. Consistent trends in the rates of scintillation and ionospheric irregularity occurrence show the potential of GNSS-RO data from commercial CubeSat missions to complement ionospheric scintillation studies undertaken by COSMIC-2 and other government agency RO missions.